Autumn in my heart - Saptarshi Basu (Vitasta Publishing, New Delhi, 2012)
Ayantika longs to become independent by becoming a bank officer whereas her mother wants her to settle down in an arranged marriage. She meets Deb online and friendship blossoms into love. In Autumn In My Heart, the author explores these areas and tries to find answers to some questions. The characters of Deb, Ayantika, Saurav, Tina, Vinod and Sagarika are finely etched and their changing relationships keep the reader spellbound.
Keywords: Fiction; English Literature